2010
DOI: 10.1186/1476-069x-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of airborne exposures generated during common cleaning tasks: a pilot study

Abstract: BackgroundA growing body of epidemiologic evidence suggests an association between exposure to cleaning products with asthma and other respiratory disorders. Thus far, these studies have conducted only limited quantitative exposure assessments. Exposures from cleaning products are difficult to measure because they are complex mixtures of chemicals with a range of physicochemical properties, thus requiring multiple measurement techniques. We conducted a pilot exposure assessment study to identify methods for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 38 publications
(37 reference statements)
2
61
0
1
Order By: Relevance
“…Additionally, task-based exposure assessment may provide a better evaluation of exposure variability, instead of assessing personal exposures using continuous 8-hour time weighted average measurements [33] and it also has a lower probability of covering exposure peaks when comparing with the time weighted average exposure over long processes or over work shifts [33]. Moreover, by using direct-reading instruments to perform task-based exposure assessment it is possible to identify more easily the tasks that represent the highest exposure risk and the ones that should have priority for applying control measures [34].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, task-based exposure assessment may provide a better evaluation of exposure variability, instead of assessing personal exposures using continuous 8-hour time weighted average measurements [33] and it also has a lower probability of covering exposure peaks when comparing with the time weighted average exposure over long processes or over work shifts [33]. Moreover, by using direct-reading instruments to perform task-based exposure assessment it is possible to identify more easily the tasks that represent the highest exposure risk and the ones that should have priority for applying control measures [34].…”
Section: Discussionmentioning
confidence: 99%
“…Peak concentrations of 2-buthoxyethanol (major ingredient of their selected sprayed products) may approach occupational exposure limits and remain in the air after completion of the cleaning task [24]. The deleterious effect of products in spray form such as waterproofing sprays [25], pesticide/insecticide sprays [26,27] or hair sprays [28] has been established for several diseases.…”
Section: Domestic Use Of Sprays and Asthma In Femalesmentioning
confidence: 99%
“…Average EGBE air concentrations estimated were 3.77 ppm (18 mg m −3 , SD = 2.24), whereas highest estimates were around 8.7 ppm (42 mg m −3 ) for mirror cleaning when a general purpose cleaner was used (Bello et al, 2013). The same authors concluded in a preceding simulation study, that EGBE air concentrations could approach OEL during cleaning activity (Bello et al, 2010). Another recent study investigating EGBE air concentrations during cleaning using a cleaning product with 7.5% EGBE, reported air concentration ranging from 4.5 to 13.5 mg m −3 (mean = 7.5 mg m −3 , SD = 3.5 mg m −3 ) (Fromme et al, 2013).…”
Section: Discussionmentioning
confidence: 65%
“…The following glycol ethers were chosen based on results from previous studies (Bello et al, 2009(Bello et al, , 2010: ethylene glycol monon-butyl ether (EGBE), diethylene glycol monoethyl ether (DEGEE), diethylene glycol mono-n-butyl ether (DEGBE), and butoxypropanol (2PG1BE), while others were included as they were listed in the safety data sheets of cleaning products used: dipropylene glycol monomethyl ether (DPGME), and phenoxyethanol (EGPhE) (Gerster et al, 2014). One exception was ethylene glycol monoethyl ether (EGEE), a glycol ether, that was never listed in safety data sheets of cleaning products.…”
Section: Introductionmentioning
confidence: 99%